Disturbed State Concept Modelling of the Resilient Modulus of Hydrated Cement Treated Crushed Rock Base for Western Australia - Khobklang, Pakdee; Vimonsatit, Vanissorn; Jitsangiam, Peerapong; Nikraz, Hamid (Khon Kaen University, 2012)
Hydrated cement treated crushed rock base (HCTCRB) is generally used as base course material for road pavement in Western Australia. Most of road pavement in Western Australia is normally designed using thin asphaltic concrete layer, therefore base layer must behave as a main flexural member that resisting the bending stress from traffic loads and pavement engineer have to design this layer carefully. Although the mechanistic approach for analysis and design of road pavement has been introduced in Australia for several decades, most of road and highway agencies in Western Australia still rely on the empirical method. However, behaviour of pavement structure can be clearly understood by using the mechanistic approach, better than using the empirical approach. Due to the mechanistic approach commonly uses the resilient modulus for analysis of structural pavement, therefore the aim of this paper is to develop a mechanistic model for predicting the resilient modulus of HCTCRB by the use of the disturbed state concept (DSC). The model was derived based on the experimental results of HCTCRB specimens which were tested by adhering the standard test method of the Austroads – APRG00/33. Then the DSC equation for predicting the resilient modulus of HCTCRB specimen, including the effect of hydration period, will be introduced. The results indicate that the use of the proposed DSC equation to back-predict the resilient modulus of HCTCRB specimens gives consistent value with the experimental results.